2010
DOI: 10.1371/journal.pone.0013271
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Discovery and Analysis of Pinewood Nematode Bursaphelenchus xylophilus by Deep Sequencing

Abstract: BackgroundMicroRNAs (miRNAs) are considered to be very important in regulating the growth, development, behavior and stress response in animals and plants in post-transcriptional gene regulation. Pinewood nematode, Bursaphelenchus xylophilus, is an important invasive plant parasitic nematode in Asia. To have a comprehensive knowledge about miRNAs of the nematode is necessary for further in-depth study on roles of miRNAs in the ecological adaptation of the invasive species.Methods and FindingsFive small RNA lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…The first nucleotide position of the known and novel mature miRNAs in the present study was found to be dominated by A and U. This is a ubiquitous phenomenon observed in miRNA studies [15,18,31,32]. This can also be taken as a putative marker for confirmation of sRNA sequences as miRNAs, and our results are also in accordance with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…The first nucleotide position of the known and novel mature miRNAs in the present study was found to be dominated by A and U. This is a ubiquitous phenomenon observed in miRNA studies [15,18,31,32]. This can also be taken as a putative marker for confirmation of sRNA sequences as miRNAs, and our results are also in accordance with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, it is estimated that approximately 20% of all human cancers, including prostate cancer (PCA), are associated with chronic inflammation [28, 50]. TLR activation, a key initiator of inflammation and dysregulation of TLR-responsive pathways, has been associated with cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Six flp genes were identified as targets of the miRNAs viz, fl-2, flp-3, flp-6, flp-12, flp-14 and flp-16. Huang et al (2010) further propose that flp genes are involved in chemically mediated interactions between B. xylophilus and its beetle vector. The expression of flp genes varied depending on the life cycle stage, for example, flp-3 is more highly expressed in the dispersal stage than in the propagative stage (Kang et al 2009).…”
Section: Neuropeptidesmentioning
confidence: 91%
“…This comes from a study on miRNAs from the pinewood nematode, Bursaphelenchus xylophilus. The miRNAs were found to be involved in the regulation of flp genes (Huang et al 2010). Six flp genes were identified as targets of the miRNAs viz, fl-2, flp-3, flp-6, flp-12, flp-14 and flp-16.…”
Section: Neuropeptidesmentioning
confidence: 99%